PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA KERJA TERHADAP KINERJA SUMBER DAYA MANUSIA (Studi Kasus pada Aparatur Sipil Negara Dinas Kependudukan dan Pencatatan Sipil Daerah Kabupaten Melawi Kecamatan Nanga Pinoh, Kalimantan Barat) - BELLA, BELLA SAFIRA B1021161114 (Jurnal Manajemen Update, 2021)
ABSTRACT THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP  AND WORK CULTURE ON HUMAN RESOURCES PERFORMANCE(A Case Study of the State Civil Apparatus, the Department of Population and Regional Civil Registration, Melawi Regency, Nanga Pinoh District, West Kalimantan) By : Bella SafiraB1021161114 Good performance is optimal, efficient and effective performance, namely performance that is in accordance with organizational standards and supports the achievement of organizational goals. Employee performance is influenced by several factors, including the Transformational Leadership Style and Work Culture. Transformational leadership style is the act of a leader who is able to change the perceptions, attitudes and behavior of subordinates regardless of whether the changes occur or not and the Work Culture leads to the unity of the shared meaning system adopted by organizational members that differentiates the organization from other organizations. Work culture in general is a philosophical statement, a function as a binding demand on employees because it can be formally formulated.This study aims to examine and analyze the effect of transformational leadership style and work culture on the performance of human resources in the Department of Population and Civil Registration, Melawi Regency, Nanga Pinoh District. The population in this study were all employees at the Department of Population and Civil Registration of Melawi Regency, Nanga Pinoh District. The sample in this study were 59 respondents. The data analysis model used is Multiple Linear Regression Analysis. Based on the results of the study, it shows that transformational leadership styles and work culture can predict or explain their effects on human resource performance. The results of the t-test study of the transformational leadership style and work culture variables have a significant effect on the performance of human resources. Keywords :   transformational leadership, work culture, and human resources performance. DAFTAR PUSTAKA A.A. Anwar Prabu Mangkunegara. (2010), Manajemen sumber daya manusia perusahaan, Bandung : Remaja Rosdakarya. Agung, Anak Wiranata (2011) Pengaruh kepemimpinan terhadap kinerja dan stress karyawan (studi kasus : CV. Mertanadi), Jurnal Nasional. Ali Shah Tazeem, Muhammad Nisar, Kashif ur-Rehman, et al (2011). Influence of Transformational Leadership on Employees outcomes: Mediating role of Empowerment. African Journal of Business Management Vol. 5, Issue 21 Baskoro. A.C. (2014). Pengaruh Kepemimpinan Transfornasional, Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan. Universitas Negeri Semarang, Indonesia. Vol. 3, No.2. Brahmasari. Ida ayu (2013). Pengaruh Motivasi Kerja, Kepemimpinan dan Budaya Kerja terhadap Kepuasan Kerja Karyawan serta Dampaknya pada Kinerja Perusahaan (Studi Kasus pada PT. Pei Hai International Wiratama Indonesia. Jurnal Manajemen. Vol 3. No. 4. Daft, Richard L. (2010). Era Baru Manajemen, Buku 2 Edisi 9. Jakarta Salemba Empat. Dessler, Gary. (2008). Human Resources Management, Fourth edition, New Jersey, Prentice Hall International. Ghozali, Imam.(2016). Aplikasi Analisis Multivariete Dengan Program IBM SPSS 23 (Edisi 8). Catatan ke VIII. Semarang: Badan Penerbit Universitas Diponegoro. Hartanto, FM. (2009). Paaradigma Baru Manajemen Indonesia : Menetapkan nilai dengan Bertumpu pada Kebijakan dan Potensi Insani, Bandung: Mizan. Hasibuan, M. (2013). Manajemen Sumber Daya Manusia. Edisi Revisi. Jakarta: Bumi Aksara. Imran Rabia, Afsheen Fatima & Arshad Zaheer, Imran Yousaf & Iram Batool (2012). How to Boost Employee Performance: Investigating the Influance of Transformational Leadership and Work Environment in a Pakistani Perspective. Iqra University Islamabad, Pakistan. Vol, 11. No. 10.   61  Khuzaeni, & Ms. Idrus, Djumahir Solimun (2013). The Influence of Work Culture, Work Stress to the Job Satisfaction and Employees Performance in the State Treasury Service Office in Jakarta, Indonesia. Faculty of Economics and Business University of Brawijaya Malang. IOSR Journal of Business and Management Vol. 9, Issue 2 Kuncoro, M. (2013). Metode Riset Untuk Bisnis dan Ekonomi. Jakarta : Erlangga. Manawan, (2017). Pengaruh Kepemimpinan Transforrmasional terhadap Kinerja Karyawan PT. BANK SULUT GO (Studi pada Bank Sulut- Go Cabang Kawangkoan). Jurnal Asministrasi Bisnis, Sulawesi Utara. Mangkunegara, Anwar Prabu. (2016). Evaluasi Kinerja Sumber Daya Manusia. Jakarta: Refika Aditama. Mathis Robert L dan John H Jackson (2012). Manajemen Sumber Daya Manusia. Penterjemah Jimmy Sadeli dan Bayu Prawira Hie. Jakarta : Penerbit PT. Salemba Empat. Nawawi. Hadari. (2008). Kepemimpinan Mengefektifkan Organisasi, Cetakan Pertama. Yogyakarta: Gadjah Mada Univercity Pres. Ndraha, Taliziduhu. (2009). Budaya Organisasi, Rineka Cipta, Jakarta. Priyatno, Duwi. (2010). Paham Analisis Statistik Data dengan SPSS. Jakarta: PT. Buku Seru. Putri, Adila. N.S & Drs. Dadang Iskandar, MM. (2016). Pengaruh Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan (Studi Kasus pada PT. Bank Rakyat Indonesia (persero) TBK Kantor Cabang Ngawi Jawa Timur. Fakultas Ekonomi dan Bisnis, Universitas Telkom. E-proceeding of Management. Vol. 3, No. 2. Raharjo, Sahid. (2013). Belajar Praktek Analisis Multivariate dengan SPSS. Klaten: E-book di download dari http://www.konsistensi.com Rees, Erik. (2001). Seven Principles of Transformational Leadership: Creating A Sinergy of Energy. Richard Y. Sangki, Kojo Christoffel & Greis M. Sendow (2014). Lingkungan Kerja, Budaya Kerja dan Semangat Kerja terhadapa Kinerja Karyawan Outsourcing pada Grapari Telkomsel Manado. Universitas Samratulangi Manado. Vol. 2 No. 3.   Ritawati, Agustina. (2013). Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap kepuasan Kerja dan Kinerja Karyawan PT. Jamsostek (Persero) Cabang Surabaya. DIE, Jurnal Ilmu Ekonomi & Manajemen Januari 2013, Vol.9 No.1. Robbins, Stephen P & Judge. T.A. (2008). Perilaku Organisasi. Edisi 16. Jakarta: Salemba Empat. Robbins, Stephen P. (2015). Perilaku Organisasi. Jilid Pertama. Edisi Sembilan. Pearson Education Asia Pte. Pt Prehallindo. Jakarta. Ruky, Achmad S. (2006). Sistem Manajemen Kinerja, Jakarta PT. Bumi Aksara. Septyan, B.F., Mochammad & Mukzam. (2017). Pengaruh Gaya Kepemimpinan Transformasional terhadap Motivasi dan Kinerja (Studi Kasus pada Karyawan CV. Jade Indopratama Malang). Fakultas Ilmu Administrasi , Universitas Braniwijaya Malang. Vol. 53, No. 1. Simamora, Hendry. (2006). Manajemen Sumber Daya Manusia, Edisi 2 dan 3, STIE YPKN. Yogyakarta. Simamora, Hendry. (2007). Manajemen Sumber Daya Manusia. Bagian Penerbitan Sekolah Tinggi Ekonomi YKPN. Yogyakarta. Sinaga, D.Susi & Nora Anisa, Br. Sinulingga. (2018). Pengaruh Motivasi, Pengawasan, dan Budaya Kerja terhadap Kinerja Karyawan pada PT. Nagalan Maju Bersama. Manajemen, Sekolah Tinggi Ilmu Ekonomi LMII. Vol. 1 No. 4. Stoner, Freeman dan Gilbert. (2003). Manajemen. Jilid II. Jakarta: PT. Indeks Gramedia Grup. Sugianingrat, Ida A.P Widani & Sarmawa (2017). Effect of Work Culture on Employee Performance With Work Motivation as Mediator: Study at Non-Star Hotel in Denpasar-Bali, Indonesia. International Journal of Economics, Commerce and Management. Vol. V, Issue 12 Sugiyono. (2017). Metode Penelitian Pendidikan (Pendekatan Kuantitatif, Kualitatif, dan R&D). Bandung: Alfabeta. Sumanto. (2014). Teori dan Aplikasi Metode Penelitian. Yogyakarta : CAPS (Center Of Academic Publishing Service). Supriyanto. (2010). Metodologi Riset Bisnis. Indeks. Jakarta. Tintami, Lila., Pradhanawati, A., Susanto, H. (2012). Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Transformasional  terhadap Kinerja Karyawan Melalui Disiplin Kerja pada Karyawan Harian SKT Megawon II PT. Djarum Kudus. Diponegoro Journal of Social and Politic. Usman, Husaini. (2011). Manajemen Teori, Praktik dan Riset Pendidikan. Jakarta: Bumi Aksara. Wibowo. (2014). Manajemen Kinerja. Jakarta : PT. Raja Grafindo Persada Widodo, Suparno. (2012). Manajemen Pengembangan Sumber Daya Manusia.Yogyakarta: PUSTAKA PELAJAR.